Kepuasan, Kepercayaan, Komitmen dan Loyalitas Mahasiswa - Asep Suhendar; Eveline Yeremia; Verra Aprilianty Mutohariatul (Jurnal Manajemen dan Bisnis, 2021)
Universities in Indonesia, including in Bandung, inspite of being a social organization, it must be able to compete with the foreign universities. Internal Marketing approach is one way to analyze the strengths of Internal Resources owned by a service company. This study examines the mediating role of satisfaction in trust and commitment relationships with loyalty in a University in Bandung. Sample size is 162 respondents whom taken by self-administered questionnaires from bureau academic staff of X University. This research shows that satisfaction is still a major consideration that cause loyalty, since there is a fully mediating role of satisfaction in trust and loyalty relationship. It means that trust should be elaborated into satisfaction firstly before turn into loyalty. The authors also make some recommendations, especially the recommendation that satisfaction is still an important factor in determining loyalty, It means that a universities in Bandung should developed employees’ satisfaction to survive in the borderless economic competition.